Shampoo Formulation Based on Banana Extract Using The Maceration Method - Winsu Broto; Fahmi Arifan; Oktaviani Kusuma Wardani; Mirza Muhammad Faisal; Arwinda Nugraheni (Diponegoro University, 2022)
To maximize the utilization of natural resources in Sugihmanik Village, especially kepok bananas, a shampoo product was made from banana peel extract. Through existing literature studies, it turns out that banana peel itself contains antioxidant flavonoids which are proven to be able to protect the scalp from attacks by free radicals and UV rays which can inhibit hair growth. These flavonoids can also repair damaged hair structures and can stimulate new hair growth, so it can be said that banana peels have the potential to become raw materials for making anti-loss shampoos. Variations in this study were modifications to the addition of extracts to 3 shampoo formulation preparations, namely 20%; 30% and 40% banana peel extract which had previously been mashed and soaked for 3 days and extracted by maceration method